GAMBARAN KLINIKOPATOLOGI POLIP HIDUNG DI POLIKLINIK THT-KL RSUP DR. M. DJAMIL TAHUN 2019-2021 - Dira, Atshyfa Zsazsa; Huriyati, Effy; Rustam, Erlina; Djosan, Al Hafiz; Endrinaldi, Endrinaldi; Intan, Shinta Ayu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Nasal polyps appear as a round, semi-transparent mass and typically develop in the middle meatus and paranasal sinuses. Histologically, nasal polyps can be divided into two subtypes, eosinophilic and neutrophilic polyps. The recurrence rate of nasal polyps is quite high, with 60-70% of patients experiencing recurrence after undergoing FESS treatment for about 18 months. The purpose of this study was to determine the clinical and histopathological characteristics of patients with nasal polyps at the THT-KL Polyclinic of Dr. M. Djamil Central Hospital in 2019-2021. This study used a descriptive design with total sampling method. The sample in this study consisted of 77 patients who met the inclusion criteria. The results of this study showed that the most frequent clinicopathological characteristics of nasal polyps in the patients were: middle-aged age group (37.66%), male gender (54.5%), sinusitis risk factor (89.61%), bilateral nature of polyps (57.14%), the most common stage was stage II (50.65%), clinical symptom of nasal congestion (98.7%), surgical management (88.31%), neutrophilic histopathological type (84.42%), with a recurrence rate of 19.48%. In conclusion, the most frequent age distribution of patients with nasal polyps was in the 41-60 age group, with the most common male gender, sinusitis risk factor, bilateral type of polyps, the most common stage was stage II, clinical symptom of nasal congestion, the most common management was surgical, histopathological type was neutrophilic, and is recurrent